Review Article: Potential of Rhizophora apiculata As Phytopharmaca - Made Ayu Wardina; Mustofa, Syazili; Malarangeng, Andi Nafisah Tendri Adjeng (Medical Profession Journal of Lampung, 2023)
Rhizophora apiculata plant is one of the true mangrove species. The Rhizophora apiculata plant is often used in traditional medicine as a slimming, anti-diarrhea and anti-vomiting drug. Several studies reported that extracts of Rhizophora species have various pharmacological activities such as antifungal, antibacterial, antiseptic, anti-inflammatory, antiulcer, and have properties in wound healing. This review article aims to determine the various potentials of the Rhizophora apiculata plant as a herbal plant which is focused on examining the various pharmacological benefits of Rhizophora apiculata as an herbal plant. The results of the study of 19 articles showed that the extract of the Rhizophora apiculata plant in the roots, bark and leaves has potential in various pharmacological activities, namely having antidiabetic abilities from the isolation of glycosin from the active dichloromethane fraction of R. apiculata, anticancer, prevention of increased total cholesterol and triglycerides, antifungal against A. niger, antibacterial against pathogens in humans, as a biolarvicide, wound healing with a wound closure value of 82.79%, anti-inflammatory activity at a concentration of 500 µg/mL which is comparable to the standard drug, namely diclofenac sodium, hepatoprotective activity that effectively reduces injury of CCl4, and antioxidant activity which has the effect of reducing MDA levels as well as a protective effect on damage to the heart, pancreas, coronary arteries, testicular, and liver in white rats induced by exposure to cigarette smoke. The protective effect on the heart, pancreas and coronary arteries is at a dose of 56.55 mg/kgBW and on the testicular and liver at an optimal dose of 113.1 mg/kgBW. The content of metabolic compounds in Rhizophora apiculata are flavonoids, glycosides, saponins, tannins, alkaloids, steroids, terpenoids, mome inositol, pigment-carotene, and pyroligneous acid. Rhizophora apiculata has the potential to be developed into phytopharmaca.